Local Government Legal Politics from Old Order, New Order, to Post-Reformation - Ida Ayu Rosida (Socio Legal and Islamic Law, 2022)
Since Indonesia's independence 76 years ago, laws on Local Government have been formed. The principle of local government implementation is contained in Article 18 paragraph (5) of the 1945 Constitution, which gives the widest autonomy to local governments in designing and implementing policies intheir regions. The term decentralization was first introduced in the Old Order era, but its implementation was only really implemented during the reform period, although it still experienced obstacles. During the New Order era, regional government was implemented using a centralized system, which was detrimental to regional autonomy. The reform period in 1998 brought significant changes with the enactment of Law Number 22 of 1999 concerning Regional Government, which affirmed the principle of broad autonomy for regions. Until now, the applicable law is Law Number 23 of 2014 concerning Regional Government.Although there have been legal developments in granting autonomy to local governments, there are still challenges in its implementation. This study aims to examine the historical journey of decentralization in Indonesia and evaluate the extent to which the principle of regional autonomy can be realized in Law Number 23 of 2014.